Santri's Emotional Intelligence and Big Five Personalities on Bullying Behaviors in Pesantren - Oktaviani, Putri; Syahid, Achmad; Moormann, Peter Paul (Jurnal Pendidikan Islam, 2020)
The purpose of this study was to examine the influence of two independent variables; emotional intelligence and big five personalities, on the dependent variable, namely the bullying behavior of teenage santri at pesantren (Islamic boarding schools) in West Sumatra. This study used a quantitative approach with multiple regression analysis methods with a significance level of 0.05 or 5%. The sample consisted of 200 santri in pesantren of West Sumatra, taken using a non-probability sampling technique. The data collection instruments used the Wong and Law's Emotional Intelligence Scale, the Big Five Inventory and the Revised Olweus Bullying/Victim Questionnaire (OBVQ). The results of this study indicate that there is a significant influence on emotional intelligence and big five personality toward bullying behavior of santri. Emotional intelligence consist of self-assessment, emotional assessment of others, emotional regulation, emotional use. The big five personality consist of extraversion, agreeableness, conscientiousness, neuroticism, openness. The hypothesis test results show that two minor hypotheses significantly affect the bullying behavior of santri in pesantren, namely the emotional regulation dimension of self-emotional assessment and the agreeableness dimension of the big five personalities.